Monoaminylation of fibrinogen and glia-derived proteins: indication for similar mechanisms in posttranslational protein modification in blood and brain - Hummerich, René; Costina, Victor; Findeisen, Peter; Schloss, Patrick (ACS chemical neuroscience, 2015)
Distinct proteins have been demonstrated to be posttranslationally modified by covalent transamidation of serotonin (5-hydropxytryptamin) to glutamine residues of the target proteins. This process is mediated by transglutaminase (TGase) and has been termed “serotonylation.” It has also been shown that other biogenic amines, including the neurotransmitters dopamine and norepinephrine, can substitute for serotonin, implying a more general mechanism of “monoaminylation” for this kind of protein modification. Here we transamidated the autofluorescent monoamine monodansylcadaverine (MDC) to purified plasma fibrinogen and to proteins from a primary glia cell culture. Electrophoretic separation of MDC-conjugated proteins followed by mass spectrometry identified three fibrinogen subunits (Aα, Bβ, γ), a homomeric Aα2 dimer, and adducts of >250 kDa molecular weight, as well as several glial proteins. TGase-mediated MDC incorporation was strongly reduced by serotonin, underlining the general mechanism of monoaminylation.
Gesehen am 24.01.2018